Differences in Aerobic Capacity and Running Speed Across Various Somatotype Structures and Body Fat Compositions among Professional Football Athletes in Indonesia - Ghozali, Dhoni Akbar; Ridhallah, Muhammad Syauqi; Shabrina, Syania; Nurhani, Ahmad Isnaini Shidqi; Hastami, Yunia; Rahayu, Dwi; Aryoseto, Lukman; Handayani, Selfi; Munawaroh, Siti; Wiyono, Nanang; Riyanto, Agus Sugeng; Budiono, Enrico Ananda; Rahma, Annisa Aghnia; Ilyas, Muhana Fawwazy (Folia Medica Indonesiana, 2024)
Highlights: 1. This study emphasizes the significance of understanding professional football players' various somatotype structures and body fat compositions as an important contribution to the area of sports science. This study lays the groundwork for future research to better understand the intricate interactions between somatotype structures, body composition, and athletic performance. 2. Since a one-size-fits-all approach may not be successful, this study advocates for tailored evaluations of training regimens to cater to athletes' unique requirements and skills, which may lead to higher overall performance. Abstract This study investigated the effects of somatotype structures and body fat composition on professional football athletes' aerobic capacities and running speed. This study used an analytical observational design with a cross-sectional approach. The subjects comprised 27 professional football athletes from Bhayangkara Football Club, located in Bekasi, Indonesia. This study measured several variables, i.e., players' age, playing position, somatotype structures assessed using the Somatotype Rating Form and Heath-Carter Somatochart, body fat composition measured using Brozek and Siri formulas, aerobic capacities determined by the maximum rate of oxygen (VO2 max) through the Yo-Yo Intermittent Recovery Test Level 2, and running speed over a 30 m distance. The data were presented as mean ± standard deviation (SD), frequency (n), and percentage. The Shapiro-Wilk was used to determine the normality of the data distribution. The statistical analyses were conducted using one-way analysis of variance (ANOVA) followed by the post-hoc least significant difference (LSD) test, the Kruskal-Wallis test followed by the post-hoc Mann-Whitney test, as well as the independent t-test, the Mann-Whitney test, and Pearson's or Spearman's correlation tests. A value of p<0.05 was considered statistically significant. The athletes exhibited a predominant somatotype structure of mesomorph-endomorph (88.9%). Notable associations were found between mesomorphy rating and running speed (r=-0.548; p=0.003), body fat composition and aerobic capacity (r=-0.448; p=0.019), as well as age and aerobic capacity (r=-0.515; p=0.006). Notably, differences in aerobic capacity were observed among various age groups (p=0.031). There were also differences in body fat composition (p=0.003) and running speed (p=0.036) between two distinct somatotype structures. These findings underscore the importance of considering individualized training and conditioning programs that account for athletes' unique body compositions and ages.